2011
DOI: 10.1088/1757-899x/18/14/142004
|View full text |Cite
|
Sign up to set email alerts
|

Origin of large thermoelectric power in off-stoichiometric Fe2VAl-based alloys

Abstract: Abstract. The valence-band and core-level soft x-ray photoelectron spectroscopy has been applied to investigate the origin of the large thermoelectric power in the off-stoichiometric and partially-substituted Fe-based Heusler-type alloys Fe 2-x-y Ir y V 1+x Al and Fe 2-x V 1+x-y Ti y Al. The non-rigid-band-like change in the valence-band electronic structure near the Fermi level E F is found for the off-stoichiometric change x in Fe and V concentrations, whereas the rigid-bandlike shift of E F is recognized on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…2. It has been also found that the simultaneous substitution by a forth element in off-stoichiometric specimens leads to increased thermoelectric power 17,18,[22][23][24] , which shows rigid-band-like dependence on the substitution from the non-rigid-band-like value of the off-stoichiometric alloy as a starting point (broken curve in Fig. 2) 18) .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…2. It has been also found that the simultaneous substitution by a forth element in off-stoichiometric specimens leads to increased thermoelectric power 17,18,[22][23][24] , which shows rigid-band-like dependence on the substitution from the non-rigid-band-like value of the off-stoichiometric alloy as a starting point (broken curve in Fig. 2) 18) .…”
Section: Introductionmentioning
confidence: 92%
“…We have experimentally investigated the total electronic density of states of off-stoichiometric Fe 2-x V 1+x Al alloys with angle-integrated soft x-ray photoelectron spectroscopy to clarify their electronic structures for thermoelectric applications 17,23,24) . Although it is dif cult to study the unoccupied states by photoelectron spectroscopy, the spectral shape near E F of the valence band of Fe 2-x V 1+x Al changes from a p-type semiconductor-like steep increase to a small shoulder feature representing the pseudogap as V increases, which qualitatively explains the observed change from p-to n-type thermoelectric power (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic structure near the Fermi level is found to be drastically altered by off-stoichiometry, while doping with Ti has a more moderate effect in a rigidband-like manner [79]. In the case of off-stoichiometric Fe 2-x V 1+x Al-based Heusler alloys, Soda et al proposed that the excess V or Fe (antisite) defects may induce impurity states near the valence band edge, resulting in a potential enhancement of the Seebeck coefficient [80]. To elucidate the anomalous p-type Seebeck coefficient in nominally n-doped Fe 2 V 1-x Mn x Al, we have performed extensive density functional theory calculations of the alloy-averaged densities of states of substituted Fe 2 V 1-x Mn x Al, which are summarized in the subsequent section.…”
Section: Fig 2 Depicts the Temperature-dependent Thermoelectric Prope...mentioning
confidence: 99%
“…The decrease of Fe from the stoichiometric value of 2.00 is known to create antisites and consequently shift the dependence of S on the VEC to the lower VEC side by creating a steep DOS slope in the conduction band near E F due to the emergence of the impurity sites. 23,24) Figure 2(c) shows the dependence of S and ρ of Fe 2 TiSi+V(2)+X(n) on the VEC when the total number of chips (n+2) was fixed to five for making the Fe amount a negligible change and the added chips (X) were V, Ti, Al, and Si. The Fe amount ranged from 1.98 to 1.99, which is almost the same as the stoichiometry.…”
mentioning
confidence: 99%